Examining social media adoption and change to the stakeholder communication paradigm in not-for-profit sport organizations - Naraine, Michael L; Parent, Milena M (Journal of Amateur Sport, 2017)
The purpose of this study was to examine social media adoption within not-for-profit sport organizations to illuminate the impetus for change, the type of change undertaken, and change resistance. Using a contextualist approach depicting the external and internal forces as well as the change process, semi-structured interviews were conducted with ten Canadian national sport organizations (NSO) representing varying degrees of social media presence. The findings suggest that, although social media is espoused as a radical, transformational vehicle, NSOs have only made incremental adjustments to their stakeholder communication and have situated social media within their extant organizational condition due to capacity constraints and resistance from staff and reticent stakeholders. Adopting social media in light of limited organizational capacity thus diminishes the utility of the communications tool. Theoretical and practical implications include how to improve social media-related capacity and the importance of continuing the social media and sport domain’s organizational theory agenda.